Laminate

The laminate structure with polycarbonate and silicone resin layers addresses adhesion issues in thermoplastic resins, ensuring durability and transparency in challenging environments.

JP2025004750APending Publication Date: 2025-01-15TORAY INDUSTRIES INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024092112
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-26
Filing Date
2024-06-06
Publication Date
2025-01-15

AI Technical Summary

Technical Problem

Conventional thermoplastic resins exhibit insufficient heat resistance and water resistance, leading to poor adhesion with difficult-to-bond materials, especially in high-temperature environments, and can cause adhesion loss and appearance defects due to crystallization and humidity.

Method used

A laminate structure comprising layers A, B, and optionally C and D, where layer A is a polycarbonate resin film, layer B contains a polycarbonate resin with a hydroxyl group and specific flow start temperature, and layer D is a silicone resin, ensuring adhesion and conformability to complex shapes while resisting water and humidity.

Benefits of technology

The laminate maintains adhesion to difficult-to-bond materials in both room and high-temperature environments, prevents adhesion loss due to water and humidity, and maintains transparency, making it suitable for complex shapes and electronic device parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025004750000001_ABST
    Figure 2025004750000001_ABST
Patent Text Reader

Abstract

To provide a laminate which generates no adhesive failure and no poor appearance by an effect of exposure to water and humidity while keeping adhesion force to a hardly adhesive material under ordinary temperature and high temperature environments.SOLUTION: A laminate includes at least a layer A and a layer B, where the layer A is a film containing 90.0 mass% or more of a polycarbonate resin, the layer B contains 90.0 mass% or more of a polycarbonate resin, the laminate has a total light transmittance of 70% or more after immersing in an aqueous solution at a temperature of 95°C containing a surface active agent, a silicone resin adheres on a surface A formed by the layer A in two surfaces of the laminate by a coating weight of 0.01 kcps or more and 0.2 kcps or less, and a value of adhesion force between the surface A bonded with an adherend on a surface B formed by the layer B and the adherend, an adhesion force between the surface A after immersing in an aqueous solution at a temperature of 95°C containing a surface active agent and the adherend, and an adhesion force between the surface A under an environment at 100°C and the adherend are respectively 5.0 N / cm or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate. [Background technology]

[0002] Adhesives and pressure sensitive adhesives are generally used to bond substrates such as films and papers. Hot melt adhesives containing thermoplastic resins are used as adhesives. Hot melt adhesives can be divided into rubber-based, acrylic-based, and silicone-based types based on the materials used, and into organic solvent solutions, emulsions, solids (hot melt, etc.), and aqueous solutions based on the state of the adhesive.

[0003] Next, the main uses of hot melt adhesives include bonding difficult-to-adhere materials (polycarbonate: PC, polypropylene: PP, polyethylene: PE, polytetrafluoroethylene: PTFE, ethylene propylene diene rubber: EPDM, etc.), temporary bonding (adhesive processing of nameplates, as well as adhesive coatings for labels and films), primary processing of adhesive materials (double-sided adhesive tapes, etc.), and removable adhesion (where re-adhesion and easy peeling are required more than temporary adhesion), so it is necessary to select a hot melt adhesive that is suitable for each application.

[0004] On the other hand, in recent years, there has been a demand for adhesives that can conform to the complex shapes of electronic device parts, maintain adhesive strength in high temperature environments exceeding 100°C for repairing heater components in home appliances, and prevent a decrease in adhesive strength and poor appearance due to humid environments or getting wet. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2013-249474 A Summary of the Invention [Problem to be solved by the invention]

[0006] In response to the above requirements, conventional thermoplastic resins have insufficient heat resistance and water resistance, and there is a problem in maintaining adhesion to poorly adhesive materials in high-temperature environments. Therefore, a proposal has been made to crystallize thermoplastic resins to improve heat resistance and water resistance (Patent Document 1). However, it is necessary to change the thermoplastic resin to suit various poorly adhesive materials, and since the thermoplastic resin hardens at room temperature, there are problems such as the inability to follow complex shapes and reduced adhesion. In addition, crystallization may cause the thermoplastic resin to turn white, resulting in poor appearance (opacity). In order to solve such problems, the objective is to provide a laminate that maintains adhesion to poorly adhesive materials both at room temperature and at high temperatures, can follow complex shapes, and suppresses the occurrence of poor adhesion and poor appearance due to the influence of water wetting and humidity. [Means for solving the problem]

[0007] As a result of intensive research to solve the above problems, the inventors have found that the problems can be solved as follows, and have arrived at the present invention. That is, the laminate of the present invention is as follows. (1) A laminate having at least a layer A and a layer B, wherein the layer A is a film containing 90.0% by mass or more of a polycarbonate resin, and the layer B contains 90.0% by mass or more of a polycarbonate resin, the laminate has a total light transmittance of 70% or more after immersion in an aqueous solution containing a surfactant at a temperature of 95°C, a silicone resin is adhered to the surface A formed by the layer A among the two surfaces of the laminate, and the amount of the silicone resin adhered is 0.01 kcps or more and 0.2 kcps or less, and the value of the adhesion strength between the surface A and the adherend after laminating the adherend to the surface B formed by the layer B among the two surfaces of the laminate, the value of the adhesion strength between the surface A and the adherend after immersion in an aqueous solution containing a surfactant at 95°C, and the value of the adhesion strength between the surface A and the adherend in a 100°C environment are all 5.0 N / cm or more. (2) The laminate according to (1), wherein the polycarbonate resin contained in Layer B contains a hydroxyl group in its molecular chain, the flow initiation temperature of Layer B is 110° C. or more and 150° C. or less, and the thickness of Layer B is 5 to 40 μm. (3) The laminate according to (1) or (2), characterized in that the laminate comprises at least a Layer A, a Layer B, a Layer C, and a Layer D in this order, wherein the Layer C contains 45.0% by mass or more of a polyethylene terephthalate resin, and the Layer D contains 90.0% by mass or more of a silicone resin. (4) The laminate according to (3), wherein the peel strength between the layer B and the layer C is 0.1 N / cm to 1.0 N / cm. (5) A laminated structure obtained by laminating the laminate according to any one of (1) to (4) and an adherend, wherein the adherend contains a polycarbonate resin, and the content of the polycarbonate resin in the entire adherend is 50.0 mass% or more. Effect of the Invention

[0008] According to the present invention, it is possible to provide a laminate that maintains adhesion to poorly adhesive materials both in room temperature and high temperature environments, can conform to complex shapes, and further suppresses the occurrence of poor adhesion and poor appearance due to the effects of getting wet or humidity. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic diagram of a laminate including a layer A and a layer B. [Diagram 2] FIG. 2 is a schematic diagram of a laminate including a layer A, a layer B, a layer C, and a layer D in this order. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The laminate of the present invention has at least a layer A and a layer B, wherein the layer A is a film containing 90.0% by mass or more of a polycarbonate resin, and the layer B contains 90.0% by mass or more of a polycarbonate resin, and the total light transmittance of the laminate after immersing the laminate in an aqueous solution containing a surfactant at a temperature of 95°C is 70% or more, a silicone resin is adhered to the surface A formed by the layer A among the two surfaces of the laminate, and the amount of the silicone resin adhered is 0.01 kcps or more and 0.2 kcps or less, and the value of the adhesion strength between the surface A and the adherend after laminating the adherend to the surface B formed by the layer B among the two surfaces of the laminate, the value of the adhesion strength between the surface A and the adherend after immersion in an aqueous solution containing a surfactant at 95°C, and the value of the adhesion strength between the surface A and the adherend in a 100°C environment are all 5.0 N / cm or more.

[0011] With the above-mentioned configuration, the laminate of the present invention maintains adhesion to the adherend, which is a poorly adhesive material, both in normal temperature and high temperature environments, can conform to complex shapes, and further suppresses the occurrence of poor adhesion and poor appearance due to the influence of water wetting and humidity. A preferred embodiment of the laminate of the present invention will be specifically described below. In the present invention, normal temperature refers to 10°C to 25°C, and high temperature refers to 80°C to 120°C.

[0012] (Description of the substrate) The above-mentioned adherend is not particularly limited, but it is assumed that the material is difficult to adhere because of the use of hot melt adhesion. More specifically, for example, molded products made of polycarbonate (PC), polypropylene (PP), polyethylene (PE), polytetrafluoroethylene (PTFE), and ethylene propylene diene rubber (EPDM) can be mentioned, among which polycarbonate (PC) is suitable for heat-resistant and water-resistant applications and is preferably used. The adherend may contain multiple materials. In addition, when the adherend contains multiple materials, that is, when the adherend contains multiple types of resins, it is preferable that one of the multiple types of resins is polycarbonate resin. The content of the polycarbonate resin is preferably 50.0% by weight or more, and more preferably 60.0% by weight or more, based on the total amount of the adherend. As described later, when the polycarbonate resin is contained in an amount of 90.0% by weight or more based on the total amount of layer B, the adhesion between the adherend and layer B can be improved by the adherend containing a specific amount of polycarbonate resin. The shape of the adherend is not particularly limited, but a sheet shape is preferably used.

[0013] Next, the laminate of the present invention will be described with reference to the drawings. FIG. 1 shows a schematic diagram of a laminate including a layer A and a layer B. FIG. 1 shows a laminate in which a layer A (designated by reference number 1) and a layer B (designated by reference number 2) are laminated. FIG. 2 shows a schematic diagram of a laminate in a different embodiment from the laminate shown in FIG. 1. That is, FIG. 2 shows a laminate in which a layer A (designated by reference number 1), a layer B (designated by reference number 2), a layer C (designated by reference number 3), and a layer D (designated by reference number 4) are laminated in this order.

[0014] (Layer B: Hot melt adhesive layer) The layer B of the present invention is a layer of a hot melt adhesive. Here, the hot melt adhesive refers to an adhesive that melts at a certain temperature or higher and develops adhesiveness. In other words, it is an adhesive that melts by applying heat to bond substrates and the like, and a thermoplastic resin is often used. And, the above-mentioned layer B preferably contains a polycarbonate resin. By using a hot melt adhesive containing a polycarbonate resin in the layer B of the present invention, it is good in terms of adhesion to the adherend to be bonded and heat resistance. Furthermore, the flow start temperature of the layer B is preferably 110 ° C or more and 150 ° C or less. If the flow start temperature is 110 ° C or more and 150 ° C or less, the adhesive does not melt in a high temperature environment, so that the adhesiveness can be maintained and the substrate and the adherend can be prevented from peeling off due to heat. In addition, when multiple resins and additives are mixed in the layer B, there may be multiple flow start temperatures, but in the present invention, the lowest melt start temperature is taken as the melt start temperature of the layer B.

[0015] Layer B of the laminate of the present invention preferably contains at least one resin selected from the group consisting of polyester resin, (meth)acrylic resin, polyolefin resin, ethylene-vinyl acetate copolymer resin, polyamide resin and chloroprene resin in addition to polycarbonate resin, and further, these polycarbonate resins and resins other than polycarbonate resins preferably have an aromatic skeleton. Having an aromatic skeleton improves the cohesive force of the resin constituting Layer B, and improves the adhesive strength with Layer A and the adherend, which is preferable. Layer B may contain only one type of resin other than the above-mentioned polycarbonate resin, or may use multiple resins.

[0016] In the present invention, Layer A, which will be described later, contains 90.0% by weight or more of polycarbonate resin, and Layer B contains 90.0% by weight or more of polycarbonate resin. In the above case, when Layer B contains 90.0% by weight or more of polycarbonate resin, it is possible to improve the adhesion to Layer A, which will be described later, and to an adherend, and it is possible to suppress the occurrence of peeling between Layer B and Layer A during, for example, shear processing. In addition, when Layer B contains 90.0% by weight or more of polycarbonate resin, it is possible to maintain the transparency of Layer B.

[0017] The method for identifying the resin of layer B is not particularly limited, but for example, layer B alone is cut out, and an IR spectrum is measured using an ATR method (see JIS K0117:2017) of a Fourier transform infrared analyzer: commonly known as an FT-IR analyzer (e.g., Shimadzu Corporation, IR Spirit), and the IR spectrum is compared with a standard sample spectrum previously recorded in a database, thereby identifying the resin. In addition, a mass spectrum of molecular ions and decomposition ions of layer B is measured using a thermal analysis gas chromatograph mass analyzer: commonly known as a GC-MS analyzer (e.g., Shimadzu Corporation, GCMS-QP2020NX), and the resin can be quantified by comparing it with a general compound spectrum previously measured using a calibration curve.

[0018] The polycarbonate resin of Layer B can be synthesized and produced by a general method, although it is not particularly limited. For example, there are a melt polymerization method in which raw materials and a catalyst are charged and heated at a temperature equal to or higher than the melting point of the product, a solid-phase polymerization method in which polymerization is performed at a temperature equal to or lower than the melting point of the product, and a solution polymerization method in which a solvent is used. Any method may be adopted, but the melt polymerization method is preferred in order to obtain a polycarbonate with an appropriate degree of polymerization that meets the object of the present invention and from the viewpoint of economy.

[0019] The thickness of Layer B is preferably 5 to 40 μm, and more preferably 10 to 35 μm. When the thickness of Layer B is 5 μm to 40 μm, the adhesive strength between Layer B and the adherend is improved, and thus it is possible to suppress the detachment of Layer B due to scratches during processing and the generation of pinholes in Layer B. In addition, when the laminate is cut to a predetermined size with a slit blade, a Thomson blade, or the like, it is possible to prevent Layer B from adhering to the surface of the slit blade or the Thomson blade.

[0020] The polycarbonate resin used in the present invention can be easily obtained by either a known transesterification method in which an aromatic dihydroxy compound is reacted with a carbonic acid diester in the presence of a transesterification catalyst such as a basic compound, or a known interfacial polycondensation method in which the aromatic dihydroxy compound is reacted with phosgene or the like in the presence of an acid binder.

[0021] Specific examples of aromatic dihydroxy compounds include bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)octane, bis(4-hydroxyphenyl)phenylmethane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, bis(4-hydroxyphenyl)diphenylmethane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxy-3-t-butylphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-phenylphenyl)propane, and 2,2-bis(3-cyclohexyl-4-hydroxyphenyl)propane. 2,2-bis(4-hydroxy-3-bromophenyl)propane, 2,2-bis(3,5-dibromo-4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclopentane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 2,2-bis(4-hydroxy-3-methoxyphenyl)propane, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxy-3,3'-dimethyldiphenyl ether, 4,4'-dihydroxydiphenyl sulfide, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfide, 4,4'-dihydroxydiphenyl sulfoxide, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfoxide, 4,4'-dihydroxydiphenyl sulfone, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfone, and the like.

[0022] Among these, 2,2-bis(4-hydroxyphenyl)propane (i.e., bisphenol A) is more preferred from the viewpoints of impact resistance and heat resistance when made into a polycarbonate resin, stability as an aromatic dihydroxy compound, and ease of availability despite the fact that it contains a small amount of impurities. In the present invention, a combination of two or more of the above aromatic dihydroxy compounds may be used as necessary.

[0023] Examples of the carbonic acid diester include aromatic carbonic acid diesters such as diphenyl carbonate, ditolyl carbonate, bis(2-chlorophenyl) carbonate, m-cresyl carbonate, dinaphthyl carbonate, and bis(4-phenylphenyl) carbonate. In addition, dimethyl carbonate, diethyl carbonate, dibutyl carbonate, dicyclohexyl carbonate, and the like can also be used as desired. Among these, diphenyl carbonate is preferred from the standpoints of reactivity, stability against coloration of the resulting resin, and cost.

[0024] The polycarbonate resin used in the present invention may be synthesized by an interfacial polymerization method or a melt polymerization method, or may be synthesized by a method such as a solid-phase polymerization method or a thin-film polymerization method. In addition, it is preferable that at least a part of the polycarbonate resin is blocked with an end group derived from a hydroxy compound.

[0025] The proportion of the terminal groups is preferably 60 mol% or more based on the total amount of terminals, and the terminal hydroxyl group concentration can be measured by spectroscopic measurement using a Ti complex. Furthermore, the terminal hydroxyl group concentration can also be measured by 1H-NMR analysis. The terminal hydroxyl group concentration according to the same evaluation is preferably 1,500 ppm or less, and more preferably 1,000 ppm or less. If the hydroxyl group terminals are within this range or the amount of blocked terminals is within this range, there is a tendency that a sufficient effect of high molecular weight can be obtained by the ester exchange reaction with the diol compound.

[0026] In view of the above circumstances, it is preferred that Layer B contains at least a polycarbonate resin, this polycarbonate resin contains a hydroxyl group in its molecular chain, the flow initiation temperature of Layer B is 110° C. or more and 150° C. or less, and further, the thickness of Layer B is 5 to 40 μm. By providing Layer B with the above characteristics, the adhesive strength with an adherend that is a poorly adhesive material is maintained both in a normal temperature environment and a high temperature environment, the layer B can conform to a complex shape, and further the occurrence of poor adhesion and poor appearance due to the influence of water wetting or humidity is suppressed.

[0027] (Layer A: polycarbonate resin-containing film) The layer A used in the present invention is a plastic film from the viewpoints of dimensional stability and durability. Examples of the resin component of the plastic film include polyester, polyolefin, polyamide, polyesteramide, polyether, polyimide, polyamideimide, polystyrene, polycarbonate, poly-ρ-phenylene sulfide, polyether ester, polyvinyl chloride, and poly(meth)acrylic acid ester. Copolymers, blends, and further crosslinked compounds of these can also be used. The layer used in the present invention is a film containing 90.0% by weight or more of polycarbonate resin. Such a film is excellent in conformity to the adherend and transparency. By containing 90.0% by weight or more of polycarbonate resin in the layer A and further containing 90.0% by weight or more of polycarbonate resin in the layer B, the adhesion between the layer A and the layer B is excellent, and for example, peeling between the layer B and the layer A during shear processing can be suppressed. That is, the layer A is a film containing 90.0% by weight or more of polycarbonate resin.

[0028] The thickness of the layer A used in the present invention is not particularly limited, but is preferably 500 μm or less from the viewpoint of ensuring flexibility, and is preferably 10 μm or more from the viewpoint of ensuring strength against tension and impact. In addition, from the viewpoint of ease of processing and handling of the film, the thickness is preferably 20 to 300 μm, more preferably 30 to 250 μm.

[0029] (Layer C: Plastic film) In the laminate of the present invention, in addition to Layer A and Layer B, it is preferable to have Layer C and Layer D. Here, Layer C that can be used in the present invention is not particularly limited, but is preferably, for example, a plastic film, synthetic paper, paper, or a composite sheet that has been subjected to a surface treatment, and among these, a plastic film is preferable in terms of dimensional stability, durability, etc. Examples of the material of the plastic film include polyester, polyolefin, polyamide, polyesteramide, polyether, polyimide, polyamideimide, polystyrene, poly-ρ-phenylene sulfide, polyether ester, polyvinyl chloride, and poly(meth)acrylic acid ester, and copolymers, blends, and further crosslinked compounds thereof can also be used.

[0030] Furthermore, among the above plastic films, films made of polyester, such as polyethylene terephthalate, polyethylene 2,6-naphthalate, polyethylene α,β-bis(2-chlorophenoxy)ethane 4,4'-dicarboxylate, polybutylene terephthalate, polycarbonate, etc. are preferred, and among these, when mechanical properties, quality such as workability, and economical efficiency are taken into consideration comprehensively, films containing 45.0 mass % or more of polyethylene terephthalate resin are more preferred. are particularly preferably used. Layer C may be made of polyethylene terephthalate resin only.

[0031] The thickness of Layer C used in the present invention is not particularly limited, but is preferably 500 μm or less from the viewpoint of ensuring flexibility, and is preferably 10 μm or more from the viewpoint of ensuring strength against tension and impact. Furthermore, when the above-mentioned plastic film is used for Layer C as a substrate, the thickness is preferably 20 to 300 μm, more preferably 30 to 250 μm, from the viewpoint of ease of processing and handling of the film.

[0032] Before laminating layer B on the surface of layer C side of laminate layer C / layer D, it is preferable to perform hydrophilization treatment to activate the surface of layer C and improve surface properties such as adhesion and coatability (wettability). By performing hydrophilization treatment, the hydrophilic functional group formed on the surface of layer C side of activated laminate layer C / layer D reacts with the hydroxyl group of layer B, resulting in improved adhesion between layer B and layer C. By improving the adhesion between layer B and layer C, peeling between layer B and layer C is more suppressed when the laminate of layer B / layer C / layer D is pulled out from the roll, while separation between layer B and layer D is possible, so that loss of a part of the laminate of layer B / layer C / layer D can be more suppressed even after the laminate is pulled out from the roll. In particular, by more suppressing the occurrence of peeling between layer B and layer C, loss of a part of layer B in the laminate is suppressed. And, because of the above circumstances, the loss of a part of layer B is suppressed, and the surface opposite to the surface of layer C side of layer B of the laminate can be adhered to layer A with stronger adhesion, so that a layer A / layer B / layer C / layer D laminate can be formed. In addition, by carrying out the hydrophilization treatment, the adhesion between layer B and layer C is improved, and the occurrence of peeling between layer B and layer C can be further suppressed, especially when the laminate is pulled out from the roll. This allows the thickness of layer D, which has a releasing effect that plays a role in suppressing the occurrence of peeling between layer B and layer C, to be thin. And, this allows the amount of silicone resin transferred between layer A / layer B to be reduced, and the adhesion between layer A / layer B and the adherend can be further improved after peeling between layer A / layer B and layer C / layer D and adhering layer B of layer A / layer B to the adherend.

[0033] The hydrophilization treatment here can be selected from discharge treatments such as plasma treatment and corona discharge treatment, treatments to improve adhesion and printability by imparting hydrophilicity to the surface by flame treatment, and treatments to form a thin drug film having hydrophilic groups. Among these, corona discharge treatment is preferably used in the present invention because of its high treatment speed and high hydrophilization effect. Specifically, the corona discharge treatment here is a method in which a film is passed between an electrode used for treatment and a treatment roll serving as an opposing electrode, and a high-frequency high voltage is applied between the electrodes to generate a corona discharge, which is brought into contact with the surface of the film, thereby generating hydrophilic functional groups on the surface of the film, thereby modifying the surface, i.e., hydrophilizing the film. The purpose of such corona discharge treatment is to effectively perform secondary processing after the corona discharge treatment process, so that, for example, in the film processing process, the film that has been subjected to corona discharge treatment is placed in the production line so that the next processing can be performed continuously.

[0034] The intensity of the corona discharge treatment may be any desired intensity depending on the film to be treated with corona discharge, and is not particularly limited, but is usually about 200 to 2000 W. If the intensity of the corona discharge treatment is too low, it tends to be difficult to obtain a stable corona discharge effect over the entire width of the film to be treated with corona discharge, while if it is too high, it is undesirable because the generated heat tends to easily cause wrinkles in the film to be treated with corona discharge, although this varies depending on the heat resistance of the film to be treated with corona discharge.

[0035] The peel strength between the layer B and the layer C is not particularly limited, but is preferably 0.1 N / cm to 1.0 N / cm in consideration of preventing the film from falling off during transport and peelability during use.

[0036] (Layer D: Release layer) In the laminate of the present invention, in addition to layer A and layer B, it is preferable to have layer C and layer D. Here, layer D that can be used in the present invention is preferably mainly composed of silicone resin in order to impart releasability. Here, "mainly composed of silicone resin" means that when all components constituting layer D are 100.0% by mass, the content of silicone resin in layer D is 90.0% by mass or more. Since layer D is mainly composed of silicone resin, it is possible to impart releasability, and when the layer B / layer C / layer D laminate is pulled out from the roll, it is possible to suppress the occurrence of peeling between layer B and layer C, while allowing separation between layer B and layer D, so that the layer B / layer C / layer D laminate can be maintained, and the surface opposite to the layer C side surface of layer B can be bonded to layer A. In the layer B / layer C / layer D laminate in a roll form, layer B is adjacent to layer D and layer C.

[0037] The content of the silicone resin in Layer D is preferably 90.0% by mass or more, because this makes the above-mentioned effects more pronounced.

[0038] Here, silicone resin refers to silicone-based compounds that have been generally known as silicone-based release agents. Silicone is a polymer with a main chain formed by alternating bonds between silicon and oxygen that have organic groups (such as alkyl groups and phenyl groups). For example, silicone-based compounds that have dimethylpolysiloxane as the basic skeleton are well known.

[0039] The silicone resin is not particularly limited as long as it does not impair the effects of the present invention. However, addition reaction type silicone resins, condensation polymerization reaction type silicone resins, ultraviolet curable type silicone resins, electron beam curable type silicone resins, and solventless type silicone resins are preferred, and from the viewpoint of improving productivity, addition reaction type silicone resins are more preferred, and silicone resins obtained by heat curing polydimethylsiloxane and hydrogensiloxane containing terminal vinyl groups in the presence of a platinum catalyst are even more preferred.

[0040] By making Layer D mainly composed of silicone resin, it is possible to make the surface free energy of Layer D 30 mN / m or less. By making the surface free energy of Layer D 30 mN / m or less, Layer D can be used as a release layer, and when the Layer B / Layer C / Layer D laminate is pulled out from the roll, the occurrence of peeling between Layer B and Layer C is suppressed, and Layer B and Layer D can be separated from each other, so that the Layer B / Layer C / Layer D laminate can be maintained, and the surface opposite to the surface of Layer C of Layer B can be bonded to Layer A, so that a Layer A / Layer B / Layer C / Layer D laminate can be formed.

[0041] The coating thickness of Layer D is preferably 0.02 to 0.50 μm, more preferably 0.05 to 0.30 μm, after drying. By setting the coating thickness to 0.02 to 0.50 μm, it is possible to prevent variation in the release performance within the surface of Layer D and reduce the amount of silicone migration after drying.

[0042] In view of the above, it is preferable that the laminate of the present invention has at least Layer A, Layer B, Layer C, and Layer D in this order, and that Layer D contains 90.0% by mass or more of a silicone resin.

[0043] (Method of Producing Laminate) Although the method for producing the laminate of the present invention is not particularly limited, a preferred method is described below. The method exemplified here is a method for producing a laminate including Layer A, Layer B, Layer C, and Layer D in this order.

[0044] A preferred embodiment of the production method of the present invention comprises the following steps 1 to 4 in this order. Step 1: Laminating layer D on one side of layer C. Step 2: Layer B is laminated to the Layer C side of the Layer C / Layer D laminate produced in Step 1. Step 3: Layer A is bonded to the Layer B surface of Layer B / Layer C / Layer D created in Step 2.

[0045] <Process 1> Step 1 is a step of laminating a layer D on one side of a layer C. First, a coating composition for the layer D, which is mainly composed of a silicone resin, is prepared. It is preferable to mix an organic solvent into the coating composition in order to improve the coatability to the substrate. The organic solvent is not particularly limited as long as it does not impair the effects of the present invention, and examples thereof include ethyl methyl ketone, methyl isobutyl ketone, butyl acetate, ethyl acetate, methanol, isopropanol, cyclohexanone, toluene, and xylene.

[0046] Thereafter, layer D is formed by applying a composition for obtaining layer D by a method that is not particularly limited as long as it does not impair the effects of the present invention, such as a comma coating method, an applicator method, a dip coating method, a roller coating method, a wire bar coating method, a reverse coating method, a kiss coating method, a gravure coating method, or a die coating method (U.S. Pat. No. 2,681,294), and more preferably, from the viewpoint of processability, the wire bar coating method, the reverse coating method, and the gravure coating method.

[0047] <Process 2> Step 2 is a step of laminating Layer B on the Layer C side of Layer C / Layer D prepared in Step 1. First, a coating composition for Layer B containing a polycarbonate resin as a main component is prepared. Here, the main component means that the polycarbonate resin is contained in an amount of 90.0 mass% or more when the total components constituting Layer B are 100.0 mass%. As with Layer D, it is preferable to mix an organic solvent into the coating composition from the viewpoint of improving the coatability to the substrate. The organic solvent is not particularly limited as long as it does not impair the effects of the present invention, and examples thereof include ethyl methyl ketone, methyl isobutyl ketone, butyl acetate, ethyl acetate, methanol, isopropanol, cyclohexanone, toluene, xylene, and the like.

[0048] Thereafter, the composition for obtaining layer B is preferably applied by a method such as a comma coat method, an applicator method, a dip coat method, a roller coat method, a wire bar coat method, a reverse coat method, a kiss coat method, a gravure coat method, or a die coat method (U.S. Pat. No. 2,681,294) as long as the effect of the present invention is not impaired, and layer B is formed by applying the composition. From the viewpoint of processability, the wire bar coat method, the reverse coat method, and the gravure coat method are more preferable. As described above, before layer B is laminated on the surface of the layer C side of the laminate layer C / layer D, it is preferable to carry out a hydrophilization treatment as a surface treatment on the surface. As described above, it is preferable to adopt a corona discharge treatment as the hydrophilization treatment.

[0049] <Process 3> Step 3 is a step of laminating Layer A to the Layer B surface of the Layer B / Layer C / Layer D produced in Step 2. A common production method is to match Layer A to the Layer B surface of the Layer B / Layer C / Layer D and laminate them together. During lamination, it is preferable to set the temperature of the laminating roll to 110°C or higher and lower than 150°C in order to improve the adhesiveness of Layer B.

[0050] [Applications of laminates] The laminate of the present invention can be used to perform shear processing such as slitting or punching, and then the Layer C / Layer D laminate can be peeled off and a desired adherend can be attached to the Layer B surface of the Layer A / Layer B. For example, it is preferably used for electronic device parts and heater parts of home appliances having complex shapes, and can be used as an adhesive when bonding a metal laminated film to another substrate, or can be bonded as a cover material to protect the metal part of a metal laminated film. At the same time, when the film bonded to the adhesive is punched to the desired dimensions and shape, the process can be kept clean without being contaminated.

[0051] Here, in the laminate of the present invention, of the two surfaces of the laminate, surface A formed by layer A has a silicone resin adhered thereto, and further, the amount of the silicone resin adhered is 0.01 kcps or more and 0.20 kcps or less. Note that, in the present invention, the amount of silicone resin adhered is synonymous with the amount of silicone resin transferred.

[0052] The amount of silicone resin transferred to Layer A is determined by winding up the Layer A / Layer B / Layer C / Layer D laminate into a roll, leaving it to stand for 1000 hours in an atmosphere at a temperature of 25° C. and a relative humidity of 50%, peeling off the Layer C / Layer D laminate, and measuring the peak intensity of silicon element on the surface of Layer A by wavelength dispersive X-ray fluorescence analysis at 0.01 kcps or more and 0.20 kcps or less. A silicon element peak intensity of 0.20 kcps or less, preferably 0.10 kcps or less, means that the transfer of the silicone resin of Layer D to Layer A and Layer B is suppressed, and the adhesiveness of Layer B is maintained, and the adhesion between Layer A and Layer B can be maintained. Furthermore, a silicon peak intensity of 0.01 kcps or more, and preferably 0.05 kcps or more, is a thickness that allows the silicone resin of Layer D to maintain sufficient releasability, and when the Layer B / Layer C / Layer D laminate is pulled out from the roll, separation between Layer B and Layer D can be achieved while suppressing the occurrence of peeling between Layer B and Layer C, thereby maintaining the Layer B / Layer C / Layer D laminate, and the surface of Layer B opposite the Layer C side can be adhered to Layer A, thereby forming a Layer A / Layer B / Layer C / Layer D laminate.

[0053] That is, as described above, the amount of silicone resin transferred from layer D to layer A is 0.01 kcps or more and 0.20 kcps or less. The peak intensity of silicon element measured by wavelength dispersive X-ray fluorescence analysis on the surface of layer A is synonymous with the amount of silicone resin attached to surface A formed by layer A among the two surfaces of the laminate. For example, when the peak intensity of silicon element measured by wavelength dispersive X-ray fluorescence analysis on the surface of layer A is 0.01 kcps, the amount of silicone resin attached to surface A formed by layer A among the two surfaces of the laminate is 0.01 kcps.

[0054] The effect of the transfer of the silicone resin to Layer B can be confirmed by peeling the Layer C / Layer D laminate from the Layer A / Layer B / Layer C / Layer D laminate and measuring the adhesion between Layer B and the adherend. The method for measuring the adhesion is not particularly limited, but for example, the Layer C / Layer D laminate is peeled from the Layer A / Layer B / Layer C / Layer D laminate, and a polycarbonate (PC) film "Iupilon" (registered trademark) (Type NF2000) manufactured by Mitsubishi Gas Chemical Company is laminated on the Layer B surface of the Layer A / Layer B laminate, and then a sample for adhesion measurement is prepared by performing a thermal bonding process using an MLP-600W type laminator manufactured by MCK Corporation at a laminator temperature of 140°C, a line speed of 0.5 m / min, and a line pressure of 2 kgf cm. The test piece for adhesion measurement is left in a thermostatic chamber at 23°C for 1 hour, and then the adhesion can be measured using an autograph manufactured by Shimadzu Corporation under conditions of a pinched peel angle of 180° and a peel speed of 50 mm / min by pinching the Layer A and the PC film, and the adhesion is preferably 5.0 N / cm or more, more preferably 7.0 N / cm or more. If the adhesion strength is 5.0 N / cm or more, peeling between Layer A and Layer B or Layer B and the adherend can be prevented when Layer B and the adherend are laminated together and then sheared, and peeling between Layer A and Layer B or Layer B and the adherend can be prevented during transport in the process. The adhesion strength obtained by this measurement is "Adhesion Strength 1 Room Temperature (N / cm)" in Table 2. The laminate of the present invention has an adhesion strength of 5.0 N / cm or more measured after an adherend is laminated to the Layer B surface side of the laminate, but the adhesion strength referred to here is "Adhesion Strength 1 Room Temperature (N / cm)".

[0055] The adhesion between layer B and the adherend at high temperatures can be measured using the same sample as above, using a thermostatic chamber attached to the autograph manufactured by Shimadzu Corporation used in the adhesion measurement, in an environment of 120°C, and the adhesion is preferably 5.0 N / cm or more, more preferably 7.0 N / cm or more. If the adhesion is 5.0 N / cm or more, it is possible to prevent peeling between layer A and layer B, or layer B and the adherend, when the layer B and the adherend are laminated and then sheared, and also to prevent peeling between layer A and layer B, or layer B and the adherend during the process transport. The adhesion obtained by this measurement is "Adhesion 2 High Temperature (N / cm)" in Table 2.

[0056] In order to prevent the laminate of the present invention from impairing the conformability to the adherend or the design of the adherend, it is preferable that the laminate maintains its adhesive strength and is transparent under normal and high temperature environments. It is also preferable that the laminate maintains its adhesive strength and transparency when wetted with water.

[0057] The adhesion strength when wet was measured by cutting the laminate to an appropriate size, laminating it on the layer B side with a polycarbonate (PC) film manufactured by Mitsubishi Gas Chemical Co., Ltd., and then using a laminator, heat bonding was performed at a laminator temperature of 140°C, a line speed of 0.5 m / min, and a line pressure of 2 kgf·cm to create a sample for adhesion measurement, and the test piece for adhesion measurement was left in a thermostatic chamber at 23°C for 1 hour. Then, an aqueous solution containing 10 wt% of a surfactant, a quaternary ammonium salt, was prepared, and the aqueous solution was heated to 95°C, after which the test piece for adhesion measurement was immersed in water for 1 hour. After that, it was removed from the aqueous solution, and the adhesion strength was measured using an autograph manufactured by Shimadzu Corporation, with layer A and the PC film pinched at a peel angle of 180 degrees and a peel speed of 50 mm / min. The adhesion strength obtained from this measurement is "Adhesion Strength 3 Water Resistance (N / cm)" in Table 2. The laminate of the present invention is prepared by laminating an adherend to the Layer B side of the laminate to obtain a laminate of the laminate and the adherend (i.e., a laminate structure), and the adhesion value of the laminate structure after immersing it in an aqueous solution containing a surfactant at 95°C or higher is 5.0 N / cm or more. The adhesion referred to here is "adhesion strength 3 water resistance (N / cm)".

[0058] The transparency of the laminate of the present invention can be determined by the total light transmittance of the laminate. The total light transmittance is obtained by measuring using a haze meter (SH7000 manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS K7361-1:1997. The total light transmittance obtained is the "room temperature 20°C" of "total light transmittance (%)" in Table 2. This total light transmittance is preferably 70% or more and 99% or less. When this total light transmittance is 70% or more, the design of the adherend can be maintained after the laminate of the present invention is bonded to the adherend.

[0059] Furthermore, the transparency when wetted with water can be determined by the total light transmittance of the laminate, and the laminate of the present invention has a total light transmittance of 70% or more after immersing the laminate in an aqueous solution containing a surfactant at a temperature of 80°C or more. The transparency when wetted with water means that the total light transmittance is within the above range when an aqueous solution in which 10 wt% of a quaternary ammonium salt as a surfactant is dissolved is prepared, the aqueous solution is heated to 95°C, the laminate is immersed in the aqueous solution for 1 hour, and the laminate is removed from the aqueous solution and measured within 30 seconds. The total light transmittance was measured using a haze meter (SH7000 manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS K7361-1:1997. The total light transmittance obtained by this measurement is "high temperature 95°C" in "total light transmittance (%)" in Table 2. If the total light transmittance is 70% or more, the laminate will not cause any appearance defects even if it is wetted with water in a high-temperature environment after being bonded to an adherend using the laminate of the present invention, and the design of the adherend can be maintained.

[0060] Moreover, the laminate of the present invention has a total light transmittance of 70% or more after being immersed in an aqueous solution containing a surfactant at a temperature of 95° C. If the total light transmittance is 70% or more, the design of the adherend can be maintained after the laminate of the present invention is bonded to the adherend. From the above viewpoint, the total light transmittance is preferably 75% or more, and more preferably 80% or more.

[0061] In addition, in the laminate of the present invention, the adhesion between surface A and the adherend after the adherend is bonded to surface B formed by layer B among the two surfaces of the laminate, the adhesion between surface A and the adherend after immersion in a 95°C aqueous solution containing a surfactant, and the adhesion between surface A and the adherend in a 100°C environment are all 5.0 N / cm or more. By having these adhesion values ​​of 5.0 N / cm or more, the adhesion between the laminate of the present invention and the adherend can be maintained even in a room temperature or high temperature environment and when wet with water. From the above viewpoint, it is preferable that these adhesion values ​​are all 5.0 N / cm or more, and more preferably 7.0 N / cm or more.

[0062] Furthermore, in the laminate of the present invention, the adhesion strength measured after laminating an adherend to the Layer B side and the adhesion strength measured after immersion in an aqueous solution containing a surfactant at 95° C. or higher are both 5.0 N / cm or more. The laminate of the present invention having such characteristics can maintain adhesion strength without peeling when wetted with water in a high-temperature environment.

[0063] The laminate of the present invention is also suitable for use in laminate structures. Here, the laminate structure is formed by laminating the laminate of the present invention and an adherend. In this laminate structure, the adherend preferably contains a polycarbonate resin. By containing a polycarbonate resin, the laminate structure becomes a laminate structure with excellent heat resistance and water resistance. The content of the polycarbonate resin in the adherend is preferably 50.0% by mass or more relative to the entire adherend. By containing a polycarbonate resin at 50.0% by mass or more, peeling between Layer B and the adherend can be prevented or suppressed. EXAMPLES

[0064] The present invention will be described in more detail below with reference to examples, but the present invention is not limited thereto in any way.

[0065] (Measurement and Evaluation Methods) (1) Adhesion 1 The laminate of the present invention was cut into a size of 100 mm x 100 mm, and a polycarbonate film "Iupilon" (registered trademark) (type NF2000) manufactured by Mitsubishi Gas Chemical Company was laminated on the layer B surface of this laminate (hereinafter, this polycarbonate film "Iupilon" (registered trademark) (type NF2000) manufactured by Mitsubishi Gas Chemical Company may be referred to as PC film). Then, using an MLP-600W type laminator manufactured by MCK Corporation, thermal bonding processing was performed at a laminator temperature of 140°C, a line speed of 0.5 m / min, and a line pressure of 2 kgf cm to prepare a sample for adhesion measurement. The test piece for adhesion measurement was left in a thermostatic chamber at 23°C for 1 hour, and then adhesion measurement was performed using an autograph manufactured by Shimadzu Corporation, with layer A and the PC film pinched and peeled at a peel angle of 180° and a peel speed of 50 mm / min.

[0066] (2) Adhesion 2 The laminate of the present invention was cut into a size of 100 mm x 100 mm, and layer B was laminated to a polycarbonate (PC) film "Iupilon" (registered trademark) (Type NF2000) manufactured by Mitsubishi Gas Chemical Company, Inc., and then heat-bonded using an MLP-600W laminator manufactured by MCK Corporation at a laminator temperature of 140°C, a line speed of 0.5 m / min, and a line pressure of 2 kgf cm to prepare a sample for adhesion measurement. The test piece for adhesion measurement was left for 1 hour in a thermostatic chamber at 23°C, and then the sample was placed in a thermostatic chamber attached to an autograph manufactured by Shimadzu Corporation, which was set to 120°C and left for 1 hour. Layer A and the PC film were pinched in the thermostatic chamber, and adhesion measurements were performed at a peel angle of 180° and a peel speed of 50 mm / min.

[0067] (3) Adhesion 3 The laminate of the present invention was cut into a size of 100 mm x 100 mm, and layer B was laminated on a polycarbonate (PC) film "Iupilon" (registered trademark) (Type NF2000) manufactured by Mitsubishi Gas Chemical Co., Ltd., and then heat-bonded using an MLP-600W type laminator manufactured by MCK Corporation at a laminator temperature of 140°C, a line speed of 0.5 m / min, and a line pressure of 2 kgf·cm to prepare a sample for adhesion measurement. The test piece for adhesion measurement was left in a thermostatic chamber at 23°C for 1 hour. Then, an aqueous solution in which 10 wt% of a quaternary ammonium salt, which is a surfactant, was prepared, and the aqueous solution was heated to 95°C, after which the test piece for adhesion measurement was immersed in water for 1 hour. Then, it was removed from the aqueous solution, and the layer A and the PC film were pinched with an autograph manufactured by Shimadzu Corporation, and adhesion measurement was performed under the conditions of a peel angle of 180 degrees and a peel speed of 50 mm / min.

[0068] (4) Peel strength The laminate of the present invention was cut into a size of 100 mm x 100 mm, and the test piece for adhesion measurement was left in a thermostatic chamber at 23°C for 1 hour. After that, the adhesion was measured by pinching layers A and C using an autograph manufactured by Shimadzu Corporation at a peel angle of 180 degrees and a peel speed of 50 mm / min.

[0069] (5) Qualitative and quantitative evaluation of layers A, B, C, and the substrate [Qualitative and quantitative analysis of resins contained in layers A, B, C, and adherends] Qualitative and quantitative analysis of the resins contained in Layer A, Layer B, Layer C, and the adherend was carried out using LC / MS / MS according to the following procedure. LC / MS / MS is a mass spectrometry technique that can be applied to non-volatile compounds that are difficult to analyze using LC / MS (gas chromatograph mass spectrometer).

[0070] <Preparation of solutions of resins contained in Layer A, Layer B, Layer C, and adherend> (a) Layer A, Layer B, Layer C, or the adherend was scraped off from the laminate, and 0.04 g of each was weighed into a 25 mL measuring flask. (b) 1 mL of HFIP (1,1,1,1,3,3,3-hexafluoro-2-propanol) / chloroform (1 / 1) was added to a measuring flask to dissolve each layer. (c) After adding 2 mL of chloroform, acetonitrile was gradually added to insolubilize the resin component. (d) Acetonitrile was added to make the volume 25 mL, and the prepared solution was then diluted 100-fold with acetonitrile. (e) The 100-fold diluted solution thus prepared was filtered through a PTFE disc filter (0.45 μm), and the obtained filtrate was used as the measurement solution.

[0071] <Quality of resins contained in layers A, B, C, and adherend> (f) The solution obtained in step (e) was subjected to LC / MS / MS, and the retention time and peak area at which peaks derived from polyethylene terephthalate, polyester resin (excluding polyethylene terephthalate), or polycarbonate were detected in the chromatogram were confirmed. (g) By performing MS analysis on the peaks derived from polycarbonate resin for Layer A, Layer B, and the adherend, and on the peaks derived from polyethylene terephthalate for Layer C, the formula weights of the ions derived from polycarbonate resin or polyethylene terephthalate were confirmed.

[0072] <Preparation of standard solutions and creation of calibration curves> (h) A pre-qualified polycarbonate resin or polyethylene terephthalate sample (0.01 g) was weighed into a 10 mL measuring flask, dissolved in methanol, and adjusted to a constant volume of 10 mL to prepare a standard solution. (i) Aliquots of the standard solution were taken and diluted with methanol to obtain four standard solutions of arbitrary concentrations. (j) The standard solutions obtained in step (i) were each subjected to LC / MS / MS to confirm the peak areas of the chromatograms for each concentration. (k) A calibration curve was obtained by linear approximation of the relationship between the solution concentration and the peak area.

[0073] <Quantitative analysis of polycarbonate resin-derived or polyethylene terephthalate-derived resin contained in Layer A, Layer B, Layer C, and adherend> (l) The peak area determined in step (f) was substituted into the equation for the calibration curve obtained in step (k) to calculate the concentration of the polycarbonate resin contained in Layer A, Layer B, and the adherend, or the polyethylene terephthalate resin contained in Layer C, thereby determining the content of the polycarbonate resin or the polyethylene terephthalate resin.

[0074] Steps (a) to (g), (k), and (l) were performed with n=2, and the average value was used as the result.

[0075] This analysis was performed using an LC system: LC-20A (Shimadzu Corporation), an MS system: API4000 (AB SCIEX Corporation), and a column: Inertsil ODS-3 (2.1 × 150 mm, 5 μm) (GL Sciences Inc.) under the following conditions: column temperature: 50°C, flow rate: 0.25 mL / min, injection volume: 1 μL, ionization method: APCI (atmospheric pressure chemical ionization), detection: positive ion detection, and measurement mode: SRM (selected reaction monitoring).

[0076] (6) Measurement of hydroxyl group concentration in layer B The laminate of the present invention was prepared, and Layer B was removed from Layer A, and the Layer B composition was collected, and the organic solvent was then volatilized to prepare 1 g of Layer B composition. 1 mg of the composition was then dissolved in chloroform, a solvent for NMR measurement, and the hydroxyl group concentration was measured by measuring and analyzing the shift in excitation wavelength using an NMR "AVANCE NEO" manufactured by Hitachi High-Tech Corporation.

[0077] (7) Flow initiation temperature of layer B The laminate of the present invention is prepared, Layer B is removed from Layer A, and the layer is sampled, and the organic solvent is then volatilized to prepare a Layer B composition. Then, using a Shimadzu Corporation differential scanning calorimeter "DSC-60 Plus", the heat quantity is measured from room temperature to 400°C at a heating rate of 10°C / min, and the melting point is measured from the peak. When multiple flow-start temperatures were confirmed, the lowest temperature was taken as the flow-start temperature.

[0078] (8) Thickness measurement of layer B The laminate of the present invention was prepared, and the thickness of the laminate was measured (measurement result was a), and after removing layer C, the thickness of layer A / layer B was measured (measurement result was b), and the thickness of layer C was measured by calculating ab. Similarly, after removing layer B from layer A / layer B, the thickness of layer A was measured (measurement result was c), and the thickness of layer B was measured by calculating bc. Measurements were made using a dial gauge (7-547 series, 7050) manufactured by Mitutoyo Corporation, and samples were cut into 10 cm squares, and measurements were performed three times for each sample, and the average of the obtained values ​​was used for evaluation.

[0079] (9) Total light transmittance of laminate (at room temperature and at high temperature) The laminate of the present invention was prepared, cut into a size of 5 cm x 5 cm, and the total light transmittance at room temperature was measured using a haze meter (SH7000, manufactured by Nippon Denshoku Industries Co., Ltd.) according to JIS K7361-1:1997. Next, an aqueous solution containing 10 wt% of a quaternary ammonium salt as a surfactant was prepared, and the aqueous solution was heated to 95°C, after which the cut-out laminate was immersed in water for 1 hour. Within 30 seconds of removing the laminate from the aqueous solution, the total light transmittance at high temperature was measured using a haze meter (SH7000, manufactured by Nippon Denshoku Industries Co., Ltd.) according to JIS K7361-1:1997.

[0080] (10) Peak intensities of silicon element at the surface of layer A and layer D From the laminate of the present invention, Layer A and the Layer C / Layer D laminate were cut into 50 mm x 50 mm squares at three randomly selected locations. The peak intensities of silicon element on the obtained Layer A and Layer D surfaces were measured using a wavelength dispersive X-ray fluorescence analyzer (manufactured by Rigaku Corporation, product name "Mini-Z", output 200 W), and the average values ​​of the three locations were calculated to measure the silicone resin content on the surface of Layer A and Layer D.

[0081] Example 1 [How to create each component] The method for producing each component is described below.

[0082] First, polycarbonate resin A having a weight average molecular weight of 26,000 and a flow initiation temperature of 126°C was prepared as a coating liquid for forming layer B, and 25 mass% coating liquid H was prepared by dissolving the resin in toluene / methyl ethyl ketone (MEK) / methylene chloride = 4 / 1 / 1 (mass ratio).

[0083] Next, a layer C / layer D laminate was prepared by the following procedure. First, a layer D coating composition was prepared by mixing "DOWSIL" (registered trademark) "LTC" (registered trademark) 750A manufactured by Dow-Toray Industries, Inc., 90% by mass of an addition reaction type silicone resin, and "DOWSIL" (registered trademark) SRX212Catalyst manufactured by Dow-Toray Industries, Inc. at 10% by mass. Next, this layer D coating composition was dissolved in methyl ethyl ketone and mixed and dispersed using a homodisper (manufactured by Primix Corporation) to obtain a layer E adjustment solution with a solid content of 3.0% by mass. In addition, a polyethylene terephthalate (PET) film "Lumirror" (registered trademark) (type S10) (thickness 38 μm) manufactured by Toray Industries, Inc. was used as layer C, and the layer D adjustment solution was applied to one surface of the layer C by a gravure coating method, and after drying at 120° C., a layer C / layer D laminate having a water-repellent layer with a thickness of 0.05 μm was obtained, and this was wound into a roll.

[0084] Next, the above coating liquid H was applied to the layer C side of the laminate layer C / layer D by a die coating method, and after drying at 120°C, a layer B / layer C / layer D laminate having a layer B with a thickness of 20 μm was obtained, which was then wound into a roll.

[0085] Furthermore, a polycarbonate (PC) film "Iupilon" (registered trademark) (Type NF2000, thickness 125 μm) manufactured by Mitsubishi Gas Chemical Company, Inc. was used as Layer A, and the Layer B / Layer C / Layer D laminate was laminated with the Layer B surface facing the Layer A surface using a thermal laminator at 120° C. to produce Laminate 1. The thickness of Layer B at this time was 16 μm.

[0086] The configuration of the laminate 1 and the like are shown in Table 1, and the evaluation results of the laminate 1 are shown in Table 2.

[0087] Example 2 A thermoplastic crystalline polyester resin B ("Polyester" (registered trademark) SP-181, manufactured by Mitsubishi Chemical Corporation) having a flow starting temperature of 150°C and a weight average molecular weight of 22,000 was prepared, and mixed with polycarbonate resin A / polyester resin B in a ratio of 95 / 5 (mass ratio), and then further dissolved in toluene / MEK (methyl ethyl ketone) / methylene chloride = 4 / 1 / 1 (mass ratio) to prepare a 25 mass% coating solution I. A laminate 2 was produced in the same manner as in Example 1, except that the resin B was mixed with polycarbonate resin A / polyester resin B in a ratio of 95 / 5 (mass ratio).

[0088] Example 3 A laminate 3 was produced in the same manner as in Example 1, except that the thickness of Layer B was 8 μm.

[0089] Example 4 Laminate 4 was produced in the same manner as in Example 1, except that the thickness of Layer D was set to 0.025 μm, and before the coating solution H was applied by die coating to the Layer C surface side of the laminate of Layer C / Layer D, a corona treatment was performed with a treatment intensity of 1000 W. That is, in laminate 4 of Example 4, a surface treatment (corona treatment) was performed on the Layer C surface side of the laminate of Layer C / Layer D, which is the Layer B stacking surface.

[0090] Comparative Example 1 Laminate 5 was produced in the same manner as in Example 1, except that a polyethylene terephthalate (PET) film "Lumirror" (registered trademark) manufactured by Toray Industries, Inc. (type T60, thickness 100 μm) was used for Layer A instead of a polycarbonate (PC) film "Iupilon" (registered trademark) manufactured by Mitsubishi Gas Chemical Company, Inc. (type NF2000, thickness 125 μm).

[0091] Comparative Example 2 Laminate 6 was prepared in the same manner as in Example 1, except that polycarbonate resin A was replaced with thermoplastic amorphous polyester resin C ("Polyester" (registered trademark) LP-011, manufactured by Mitsubishi Chemical Corporation) having a flow initiation temperature of 65°C, a weight average molecular weight of 16,000, and a glass transition temperature of 4°C.

[0092] Comparative Example 3 Laminate 7 was prepared in the same manner as in Example 1, except that the Layer D preparation solution was applied to one surface of the Layer C by a gravure coating method, and then dried at 120°C to obtain a Layer C / Layer D laminate having a water-repellent layer with a thickness of 1 μm.

[0093] Comparative Example 4 A thermoplastic crystalline polyester resin B ("Polyester" (registered trademark) SP-181, manufactured by Mitsubishi Chemical Corporation) having a flow start temperature of 150°C and a weight average molecular weight of 22,000 was prepared, and this was mixed with polycarbonate resin A / polyester resin B in a ratio of 80 / 20 (mass ratio), and then further dissolved in toluene / MEK (methyl ethyl ketone) / methylene chloride = 4 / 1 / 1 (mass ratio) to prepare a 25 mass% coating solution J. Laminate 8 was produced in the same manner as in Example 1, except that coating solution J was used instead of coating solution H.

[0094] In Examples 2 to 4 and Comparative Examples 1 to 4, laminates were produced in the same manner as in Example 1, except that the composition of each layer was as shown in Table 1, and were evaluated in the same manner.

[0095] Table 1 shows the configurations of the laminates of Examples 2 to 4 and Comparative Examples 1 to 4, and Table 2 shows the evaluation results of the laminates of Examples 2 to 4 and Comparative Examples 1 to 4.

[0096] All of the laminates shown in Examples 1 to 4 satisfy the adhesion 1, adhesion 2, adhesion 3, and total light transmittance. In contrast, it was confirmed that the adhesion 1 to 3 of the laminates shown in Comparative Example 1 and Comparative Example 3 is lower than that of Example 1. It was confirmed that the adhesion (adhesion 2) in a high temperature environment and the adhesion (adhesion 3) after immersion in water of the laminate shown in Comparative Example 2 is insufficient compared to Example 1. It was confirmed that the total light transmittance of the laminate shown in Comparative Example 4 is also insufficient compared to Example 1. The evaluation results of Examples 1 to 3 and Comparative Examples 1 to 4 are shown in Table 2. Note that, in the laminates of Examples 1 to 3, all of the adhesion 1 to 3 are 5.0 N / cm or more, and these laminates have excellent conformability to the adherend.

[0097] [Table 1]

[0098] [Table 2] [Explanation of symbols]

[0099] 1: Layer A 2; layer B 3: Layer C 4: Layer D

Claims

1. A laminate having at least a layer A and a layer B, The layer A is a film containing 90.0% by mass or more of a polycarbonate resin, The layer B contains 90.0% by mass or more of a polycarbonate resin, The total light transmittance of the laminate after immersing the laminate in an aqueous solution containing a surfactant at a temperature of 95° C. is 70% or more; Of the two surfaces of the laminate, surface A formed by layer A has a silicone resin adhered thereto; The amount of the silicone resin adhered is 0.01 kcps or more and 0.20 kcps or less, The value of the adhesion strength between the surface A and the adherend after the adherend is bonded to the surface B formed by the layer B out of the two surfaces of the laminate, the value of the adhesion strength between the surface A and the adherend after immersion in an aqueous solution containing a surfactant at 95°C, and the value of the adhesion strength between the surface A and the adherend in a 100°C environment are all 5.0 N / cm or more. A laminate comprising:

2. The polycarbonate resin contained in the layer B contains a hydroxyl group in its molecular chain, The flow initiation temperature of the layer B is 110° C. or more and 150° C. or less, 2. The laminate according to claim 1, wherein the thickness of the layer B is 5 to 40 μm.

3. The laminate comprises at least a layer A, a layer B, a layer C, and a layer D in this order, The layer C contains 45.0% by mass or more of a polyethylene terephthalate resin, 3. The laminate according to claim 1, wherein the layer D contains 90.0% by mass or more of a silicone resin.

4. 4. The laminate according to claim 3, wherein the peel strength between said layer B and said layer C is 0.1 N / cm to 1.0 N / cm.

5. A laminate structure obtained by laminating the laminate according to claim 1 or 2 and an adherend, The adherend contains a polycarbonate resin, A laminate structure, characterized in that the content of the polycarbonate resin is 50.0 mass % or more based on the entirety of the adherend.

Citation Information

Patent Citations

  • Crystalline polyester resin, and adhesive composition using the same

    JP2013249474A